Enhancing Early Childhood Educator Proficiency in Implementing STEAM-Loose Parts using a Project-based Learning Model - Amri, Khairul; Syarfina, Syarfina; Veryawan, Veryawan (Program Studi Magister Pendidikan Anak Usia Dini, 2024)
Applying STEAM-based learning methods is challenging for early childhood (EC) educators because most of them need help to develop media and learning activities. This study aims to improve EC teachers' proficiency in implementing STEAM learning methods with loose-part materials through project-based learning (PjBL) models. This action research uses the Elliot model, which consists of 7 steps: initial idea identification, fact analysis, general planning, implementation, observation, evaluation, and idea improvement. The participants in this study were 15 preschool teachers from different institutions in Langsa, Aceh. Data collection techniques used observation and the instruments consisted of observation sheets and project assessment sheets. The results showed that the average score of teacher competence in cycles one and two increased. 80% of the total 15 teachers have reached the minimum success indicator. Therefore, the PjBL method is concluded to improve the competence of EC teachers in implementing STEAM method learning with loose parts. From the results of this study, it is hoped that teachers can apply it in their respective institutions to provide more comprehensive benefits to students. This study suggests that early childhood institutions should help EC teachers implement the STEAM-based loose parts. Further research can be conducted in ECE on the extend of STEAM implementation.